Strategi Guru Meningkatkan Kedisiplinan Siswa melalui Program Hafalan Surah Pendek Al-Qur’an - Afwanni, Yulia Azizah; Saputra, Edi (YASIN, 2025)
The research is motivated by the increasing number of students arriving late to school, particularly in the memorization program of short surahs from the Al-Qur'an, which is a strategy used by teachers to enhance student discipline. The aim of this study is to explore education that shapes character and discipline among students at SMA Negeri 1 Linggo Sari Baganti, Indonesia, with an emphasis on the memorization program of short surahs from the Al-Qur'an. Through this program, it is hoped that students who are late can hone their knowledge not only in intellectual aspects but also in the spiritual field. The method used in this study is descriptive qualitative, involving the principal, teachers, and students as participants. This study employs a case study approach and applies literature review methods, observation, interviews, and documentation, which are then analyzed to draw conclusions. The results indicate that: 1) The level of discipline at the school is already good, supported by the Al-Qur'an memorization program conducted daily; 2) The strategies implemented by teachers to enhance student discipline, particularly for those arriving late, include direct interaction and the obligation to memorize surahs before entering the classroom; 3) This study also identifies the factors that support and hinder the implementation of these strategies, both from internal and external factors. The main conclusion of this study emphasizes the importance of teacher strategies in improving student discipline through the memorization program of short surahs from the Al-Qur'an for late students. This approach not only sharpens intellectual abilities but also spiritual ones, within the discipline system to promote behavioral change in students and create a better learning environment. The implications of this research indicate that students participating in the memorization program of short surahs from the Al-Qur'an not only improve their discipline but can also use this program as a tool to build character and spirituality. Furthermore, the approach used by teachers to address student tardiness can serve as an example for other schools in creating a more disciplined learning environment and supporting the overall development of students.